EFEKTIVITAS KONSELING BEHAVIORAL MELALUI TEKNIK COGNITIVE RESTRUCTURING UNTUK MENGATASI PERUNDUNGAN SOSIAL PADA SISWA - Imamah, Nurul; Rofi 'Azmi, Khilman (Jurnal Bimbingan dan Konseling Borneo, 2022)
AbstractOne of the efforts to follow up on the cash us bullying students are forms implementation of good order to the school and student. Purpose of the paper is to test the effectiveness of behaviolare counseling through cognitive restructuring technique to address the bullying class of IX class students in MTs Islamiyah Blingoh. This research uses quantitative approach.The method used in this research is the True Esperiment study with the preterest-posttest control group design design.The sample of research used this study is there as many as 16 students who have medium and high bullying categories. Based on the results of the study, it is known that there is a decrease in bullying behavior after implementing the behaviolance of congestion through cognitive restructuring techniquewith obtained DF = 7 with significant level 0, 05 are 2,365, and obtained tcalculate= 32.829. Because of tcalculatettable,So (32,829 2.365), then H0 is rejected and ha is acceptable. While the control group with DF = 7 with significant level0, 05ARE 2,365, and obtained tcalculate= 1.567.because oftcalculatettable, then (1.567 2,365), then H0 accepted and H0 is rejected.So it can be concluded that by expressing effective Cognitive Restructuring techniques to address the Bullying Class of IX class students in MTS Islamiyah Blingoh.Keyword: Bullying, Cognitive Restructuring, Behavioral Counseling